Surgical hardware-related iatrogenic venous compression syndrome. (April 2015) - Mathur, Moses; Shafi, Irfan; Alkhouli, Mohamad; Bashir, Riyaz
Deep vein thrombosis related to immobilization is a common and extensively studied disorder, particularly in hospitalized patients. However, the phenomenon of iatrogenic venous compression (IAVC) and related deep venous thrombosis (DVT) is under-recognized and under-reported. In the absence of relieving the compressive pathology, the recanalization rates are expected to be very low – thereby putting patients at a significant risk for the development of post-thrombotic syndrome (PTS). In this report, we describe two cases of DVT related to IAVC, and review similar cases that have been previously reported in the literature. With advancements in catheter-based technology, patients with IAVC (with or without DVT) may now be offered advanced endovascular treatment options such as catheter-directed pharmacomechanical thrombolysis (PMT) and percutaneous venoplasty and/or stenting. Hence, timely recognition and treatment is essential in the prevention of disabling PTS or life-threatening pulmonary embolism.